Mapping the origins of figurative language in comparative literature - Trim, Richard 1950- (New York, NY Routledge, 2022)
"This book investigates the origins of figurative language in literary discourse within a cognitive framework. It represents an interface between linguistics and literature and develops a 6-tier theoretical model which analyses the different factors contributing to the creation of figurative words and expressions"--Provided by publisher.
Towards a global model of figurative origins -- Figurative creativity in language structure -- Cross-language evidence for the limits of linguistic creation -- Underlying figurative thought -- Tracing cultural history -- Theories of reference in conceptual mapping -- Textual reference in the form of narrative -- Personal biography in figurative language -- Conceptualisation of the real world -- The transformation of reality -- Multiple conceptual mapping -- The overall picture.
Includes bibliographical references and index.
Keywords: Figures of speech in literature; Discourse analysis, Literary; Figures of speech; Electronic books